(untitled) (Educational Dimension, 2020)
The article is devoted to the problem of political-linguistics education at universities of Ukraine. The place of political linguistics is defined as a new interdisciplinary branch of scientific knowledge. The necessary of learning this discipline is argued at higher education institutions, especially at the postgraduate studies (PhD’s level). The paper touches upon the problem of political discourse determination as the main subject of the political linguistics. Although it is comparatively the young discipline and the definitions of its main categories aren’t universal enough, but the learning of political linguistics and its general components comes actively into educational and scientific syllabuses of Ukrainian higher education. The aim of the article is defining of the main specific principle and features of political linguistics learning at higher educational institutions in Ukraine. Such principles and features depend directly on specific peculiarities of political discourse and the interdisciplinary character of political linguistics. The author analyzes the problem of political discourse understanding as the subject of political linguistics study and the features of its categories representations in different syllabuses. She explores the researches about the learning methodology of political linguistics and of some tangent disciplines at universities of Ukraine.